Les activités du Conseil de l’Europe en faveur des zones côtières : gestion durable du territoire et du paysage - Maguelonne Dejeant-Pons (VertigO)
The Council of Europe’s main objectives are to promote democracy, human rights and the rule of law and to seek common solutions to the main problems facing European society today. The Organisation is active in promoting sustainable spatial development in line with Recommendation Rec. (2002) 1 of the Committee of Ministers to Member States on The Guiding Principles for Sustainable Spatial Development of the European Continent (GPSSDEC-CEMAT).  These principles seek to protect the quality of life and well-being of Europeans taking into account landscape, as well as cultural and natural values. Five “heritage” conventions have been adopted to date within the framework of the Council of Europe and should be underlined whenever policy questions about the integrated management of coastal zones are mentioned.  They are the following: European Convention on the Protection of the Archaeological Heritage (London, 6 May 1969) (revised, Valletta, 16 January 1992) ; Convention on the Conservation of European Wildlife and Natural Habitats (Bern 19 September 1979) ; Convention for the Protection of the Architectural Heritage of Europe (Granada, 3 October 1985) ; and Framework Convention on the Value of Cultural Heritage for society (Faro, 20 October 2005). Other instruments are specifically devoted to coastal zones.